A Study of Policy Implementation on Appreciation for Honor Students at the Faculty of Social Science and Political Science, Brawijaya University - Ike Sophia Hanna; Agus Suryono; Suryadi Suryadi (Sekolah Pascasarjana Universitas Brawijaya, 2021)
Public policy becomes a major highlight, with consideration that the presence of students is the core of policies of higher education institutions. Public policies regarding students also become the benchmark for student development as seen through activities of student achievement. The objective of this research is to examine the process of policy implementation for appreciation for honor students in the environment of the Faculty of Social Science and Political Science of Brawijaya University (FISIP UB). This research utilized the method of qualitative research, with data and information collection conducted through the techniques of interviews, documentation, and observation. The results of this research indicated that the implementation of policies for the provision of appreciation can be seen through the various kinds of achievements that have been achieved by FISIP UB students and have been rewarded, by way of individual and group efforts, through participation in activities at the campus, provincial, national, and international levels. The objective of rewards is to motivate students to be able to be more creative and spirited in making contributions to improve the image of the faculty. The process of implementing the provision of appreciation for students is also continuously performed to elicit a maximum response from students. This is because student achievements, in addition to generating rewards in the form of money given to them or the provision of appreciation for honor students in the form of congratulations from the faculty to students through posts on the official social media channels of the faculty or banners containing information on achievements of students and personal characteristics, become examples and motivation for other students to achieve their achievements. This research concludes that the policies can increase the creativity and spirit of students in attaining achievements and contributing to the faculty.